Unseating of single-span bridges with skew angles out of the limit range for free rotation. (August 2021) - Wu, Suiwen; Huang, Junfei; Li, Weifeng; Jiao, Chiyu; Li, Jianzhong
Abstract: Past researches have indicated that skewed bridges can rotate around the obtuse corners upon gap closure and the bridge deck can rotate freely when the skew angle is within a limit range. Beyond this range, the rotation of the bridge deck could be locked against the abutments. For these bridges, girder unseating can be avoided either by geometric constraint of the deck or by providing adequate support length to account for seismic demands. In this paper, the unseating of single-span bridges is studied for skew angles out of the limit range for free rotation. To begin, the skew angle limit range for free rotation was derived for bridges with and without expansion gaps. It was found that the expansion gap has a slight influence on the skew angle limit range for free rotation. The minimum support length ( N ) of skewed bridges to reach geometric constraint (when locked against the abutments) was then derived step-by-step based on geometry. It is found that the N to reach geometric constraint increases with skew angles approximately in an exponential manner. Finally, a parametric study was performed on prototype skewed bridges using a shake table experiment-validated nonlinear model to compute the support length demands during design-level earthquakes. Nonlinear analysis was performed under seven historical near-fault records scaled to the design-level earthquakes. Comparison was made between the support length to reach geometric constraint and those from numerical analysis. The results indicate that it is very likely that a single-span bridge of any skew angle could rotate freely during the design-level earthquakes even when its geometry could allow it to be blocked by the abutments. Therefore, the minimum support length of single-span bridges should be designed based on seismic demands rather than geometric constraint when the skew angles are out of the limit range. In addition, it was also found that the Japan Road Association (JRA) is unreasonable to assume zero skew effect on the minimum support length requirements and current codes and specifications underestimate the skew factor when the skew angles fall out of the limit range.